Deletion of chr7p22 and chr15q11: Two Familial Cases of Immune Deficiency: Extending the Phenotype Toward Dysimmunity - Sloboda, Natacha; Sorlin, Arthur; Valduga, Mylène; Beri-Dexheimer, Mylène; Bilbault, Claire; Fouyssac, Fanny; Becker, Aurélie; Lambert, Laëtitia; Bonnet, Céline; Leheup, Bruno (Frontiers in Immunology, 2019)
Background: We report here two new familial cases of associated del15q11 and del7p22, with the latter underlining the clinical variability of this deletion. Two siblings patients presented a similar familial imbalanced translocation, originating from a balanced maternal translocation, with deletions of 7p22 and of 15q11 (arr[GRCh37] 7p22.3-p22.2(42976-3736851)x1, 15q11.1-q11.2(20172544-24979427)x1). Methods: We used aCGH array, FISH and karyotype for studying the phenotype of the two patients. Results: The 7p22 deletion (3,5 Mb) contained 58 genes, including several OMIM genes. Patients 1 and 2 exhibited acquisition delays, morphological particularities and hypogammaglobulinemia, which was more severe in patient 1. Patient 1 presented also with cerebral vasculitis. Conclusion: We discuss here how the PDGFa, CARD11, LFNG, GPER1 and MAFK genes, included in the deletion 7p22, could be involved in the clinical and biological features of the two patients.